Women's Underrepresentation in Science Sociocultural and Biological Considerations. [article]. - Ceci, Stephen J.
The underrepresentation of women at the top of math-intensive fields is controversial, with competing claims of biological and sociocultural causation. The authors develop a framework to delineate possible causal pathway and evaluate evidence for each. Biological evidence is contradictory and inconclusive. Although cross-cultural and cross-cohort differences suggest a powerful effect of sociocultural context, evidence for specific factors is inconsistent and contradictory. Factors unique to underrepresentation in math-intensive fields include the following : (a) Main proficient women disproportionately prefer careers is non-math-intensive fields and are more likely to leave math-intensive careers as they advance; (b) Mathematics and the Graduate Record Examinations Quantitative Reasoning sections; (c) women with high-math competence are disproportionately more likely to have high verbal competence, allowing greater choice of professions; and (d) in some math intensive fields, women with children are penalized in promotion rates. The evidence indicates that women's preferences, potentially representing both free and constrained choices, constitute the most powerful explanatory factor; a secondary factor is performance on gatekeeper tests, most likely resulting from sociocultural rather than biological causes. -- (from the author)